KONSTRUKSI PRIMER UNTUK MENGISOLASI GEN EKSOGLUKANASE BACILLUS SP. RP1 - Arif Sardi (Prosiding Seminar Nasional USM, 2019)
Primer design is a very important factor in gene isolation. The selection of the right primer will determine the success/failure of gene isolation. Information and data on exoglucanase gene sequences were obtained from www.cazy.org and www.ncbi.nlm.nih.gov. The degenerate primer design process is carried out by finding sequences of exoglucanase genes from bacteria that are taxonomically close to Bacillus. By considering some of the criteria needed to design a primer, two primer candidates were produced  at the residual position 1994-2010 and 3112-3129. The first candidate can be constructed as a forward primer and the second as a reverse primer, so the size of the PCR product resulted is ~1100 bp. In addition to the size, the alternative PCR product it is also possible to measure ~800 bp because the results of the alignment of some sequences still indicate a gap between the sequences (about 300 residues). The calculation result of the primer characteristic show that the two primers that were designed were in a fairly ideal condition. Tm  of the two primers is not too much different (forward primer 64.29ºC and reverse primer 63.79ºC) so that it can be used simultaneously in a PCR reaction.